Bacterial Outer Membrane Vesicles as a Versatile Tool in Vaccine Research and the Fight against Antimicrobial Resistance - Zhuang Zhu (American Society for Microbiology, 2021)
ABSTRACT Gram-negative bacteria include a number of pathogens that cause disease in humans and animals. Although antibiotics are still effective in treating a considerable range of infections caused by Gram-negative bacteria, the alarming increase of antimicrobial resistance (AMR) induced by excessive use of antibiotics has raised global concerns. Therefore, alternative strategies must be developed to prevent and treat bacterial infections and prevent the advent of a postantibiotic era. Vaccines, one of the greatest achievements in the history of medical science, hold extraordinary potential to prevent bacterial infections and thereby reduce the need for antibiotics. Novel bacterial vaccines are urgently needed, however, and outer membrane vesicles (OMVs), naturally produced by Gram-negative bacteria, represent a promising and versatile tool that can be employed as adjuvants, antigens, and delivery platforms in the development of vaccines against Gram-negative bacteria. Here, we provide an overview of the many roles OMVs can play in vaccine development and the mechanisms behind these applications. Methods to improve OMV yields and a comparison of different strategies for OMV isolation aiming at cost-effective production of OMV-based vaccines are also reviewed.